Economically advantageous pathways for reducing greenhouse gas emissions from industrial hydrogen under common, current economic conditions. Issue 3 (15th February 2021) - Finke, Cody E.; Leandri, Hugo F.; Karumb, Evody Tshijik; Zheng, David; Hoffmann, Michael R.; Fromer, Neil A.
Abstract : Almost all clean hydrogen that is used in industry is made by cogenerating low-cost hydrogen and other commodities. We propose a framework to make the world's hydrogen from low-cost cogeneration processes. Abstract : Hydrogen is a major industrial chemical whose manufacture is responsible for ∼3% of global carbon dioxide emissions. >95% of hydrogen is made via reforming fossil fuels which typically co-produces hydrogen and waste carbon dioxide. Nearly all other hydrogen is co-produced with other commodity chemicals. Unfortunately, many alternative, clean hydrogen production processes are small-scale because they require major reductions in capital cost or energy prices to be economical enough for industry. Because the climate problem is urgent, and the economics of future energy is uncertain, this paper seeks to expand the options for producing industrial-scale, clean hydrogen under common, present-day economic conditions. First, we build a model to understand the economic and carbon dioxide emissions constraints of sulfur electrolysis which is an emerging process that cogenerates hydrogen and co-salable sulfuric acid and has the potential to produce up to 36% of the world's current hydrogen demand under present-day, average US economic conditions. We also use our model to evaluate water electrolysis, which cogenerates hydrogen and waste oxygen, but is not economical under present-day average US economic conditions. We then propose criteria for identifying clean hydrogen production chemistries. Using these criteria, we find enough reactions to have the combined potential to make over 150% of the world's industrial hydrogen needs under present-day, average US economic conditions while reducing cost and reducing or eliminating CO2 emissions. Given the urgency of the climate problem, we believe that an economic analysis, such as this is crucial to near-term CO2 emissions reductions.